TRENDS OF ARTIFICIAL INTELLIGENCE AND IMMERSIVE DESIGN USE IN THE FORMATION OF ARCHITECTURAL ENVIRONMENT - Vergunova, N.; Blinova, M. (Municipal economy of cities. Series: «Economy science», 2024)
There is increasing attention to a new design methodology incorporating the latest achievements of a non-hierarchical way of forming based on the learning process of computers or machines, namely the concepts of artificial intelligence (AI) and immersive design, using virtual and other types of reality. The study aims to reveal the necessity to identify the main trends of artificial intelligence and immersive design use in architectural environment formation. The results can contribute to rethinking architectural design algorithms at the present stage and identifying potential opportunities for improvement. The paper describes the possibilities of AI and immersive design in architectural environment formation. Analysis of current research in this field has made it possible to identify trends that likely will continue to develop further and impact the architectural profession. One of these trends is the improvement of the architect’s toolkit, currently provided by additional plug-ins to existing programmes or separate services based on AI algorithms, but in the future, it may be a change in the programme code itself with a completely updated structure. In this case, the role of software from the architect-managed toolkit may shift to another plane, such as a digital assistant that partially or fully manages its responsibilities in working on an architectural project. The symbiosis of multidirectional but powerful immersive design technologies (VR, AR, MR) and AI algorithms is another trend in architectural environment formation. It can also be characterised as the most experimental and, at the same time, dynamically progressing, given the active development of its components. Another modern trend is to bring architectural design to a new level of a balanced combination of virtual and real. The immersion of the user in virtual reality for design work and demonstration of the relevant results is gradually changing as the 3D model of an architectural structure is increasingly manifested in the physical world, including at the implementation site, and interactive equipment with flexible and constantly evolving functionality provides architects with more opportunities for creativity.